Trade and Finance in Global Missions (16th-18th centuries) - Thanh, Hélène Vu,; Županov, Ines G., (Studies in Christian Mission ;, 2021)
"The book was drafted by Jesuits and their students of the Flemish province to commemorate the Society of Jesus's hundred years of existence. It was as much a homage to the Society's founders as a celebration of the spiritual and material achievements of its members over the century, with a particular emphasis on the order's missionary vocation. From the moment of its publication, the Imago was attacked by the Jesuits' enemies: both Protestants and Jansenists denounced the Society's arrogance as well as its casuistical methods. Here is not the place to relate the history of the work or its reception, but it seemed essential to us to highlight the significance of the emblems illustrating the book's"--